Adherence to antihypertensive medications and health outcomes among newly treated hypertensive patients - Luca Degli Esposti; Stefania Saragoni; Silvia Benemei; et al (Dove Medical Press, 2011)
Luca Degli Esposti1, Stefania Saragoni1, Silvia Benemei3, Paolo Batacchi2, Pierangelo Geppetti3, Mauro Di Bari3, Niccolò Marchionni3, Alessandra Sturani4, Stefano Buda1, Ezio Degli Esposti41CliCon S.r.l. Health, Economics and Outcomes Research, Ravenna, Italy; 2Pharmaceutical Policy Department, Local Health Unit of Florence, Florence, Italy; 3CIRFF, University of Florence, Florence, Italy; 4Outcome Research Unit. Policlinics Umberto I, Rome, ItalyObjective: To evaluate adherence to antihypertensive therapy (AHT) and the association between adherence to AHT, all-cause mortality, and cardiovascular (CV) morbidity in a large cohort of patients newly treated with antihypertensives in a clinical practice setting.Methods: An administrative database kept by the Local Health Unit of Florence (Italy) listing patient baseline characteristics, drug prescription, and hospital admission information was used to perform a population-based retrospective study including patients newly treated with antihypertensives, ≥18 years of age, with a first prescription between January 1, 2004 and December 31, 2006. Patients using antihypertensives for secondary prevention of CV disease, occasional spot users, and patients with early CV events, were excluded from the study cohort. Adherence to AHT was calculated and classified as poor, moderate, good, and excellent. A Cox regression model was conducted to determine the association among adherence to AHT and risk of all-cause mortality, stroke, or acute myocardial infarction.Results: A total of 31,306 patients, 15,031 men (48.0%), and 16,275 women (52.0%), with a mean age of 60.2 ± 14.5 years was included in the study. Adherence to AHT was poor in 8038 patients (25.7% of included patients), moderate in 4640 (14.8%), good in 5651 (18.1%), and excellent in 12,977 (41.5%). Compared with patients with poor adherence (hazard ratio [HR] = 1), the risk of all-cause death, stroke, or acute myocardial infarction was significantly lower in patients with good (HR = 0.69, P < 0.001) and excellent adherence (HR = 0.53, P< 0.001).Conclusions: These findings indicate that suboptimal adherence to AHT occurs in a substantial proportion of patients and is associated with poor health outcomes already in primary prevention of CV diseases. For health authorities, this preliminary evidence underlines the need for monitoring and improving medication adherence in clinical practice.Keywords: antihypertensive drug therapy, adherence, all-cause mortality, stroke, acute myocardial infarction